The labour market in winter the state of working Britain - Gregg, Paul; Wadsworth, Jonathan, Dr (Oxford University Press, 2011)
This text provides an overview of the key issues concerning the performance of the labour market and policy in the UK, with focus on the 2008 financial crisis, the ensuing recession, and its aftermath. It contains assessments of the effects of many policies introduced over the last 10 years in employment, education and welfare.